2019
DOI: 10.1097/cm9.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Screening of MYH7 gene mutation sites in hypertrophic cardiomyopathy and its significance

Abstract: Background: There have been few reports of mutations in the beta-myosin heavy chain (MYH7) gene in hypertrophic cardiomyopathy (HCM), which is associated with sudden cardiac death caused by HCM. This study aimed to screen the mutation sites in the sarcomeric gene MYH7 in Chinese patients with HCM. We also planned to analyze the pathogenicity of the mutation site as well as its significance in clinical and forensic medicine. Methods: From January 2006 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The atrial myocardium expresses αMYH, and the ventricular myocardium expresses βMYH. MYH7 gene variants are associated with a variety of cardiomyopathies in humans, including HCM [97] and DCM [98]. Emerging evidence also indicates that MYH6 variants may result in AF.…”
Section: Variants In Myosin Heavy Chainmentioning
confidence: 99%
“…The atrial myocardium expresses αMYH, and the ventricular myocardium expresses βMYH. MYH7 gene variants are associated with a variety of cardiomyopathies in humans, including HCM [97] and DCM [98]. Emerging evidence also indicates that MYH6 variants may result in AF.…”
Section: Variants In Myosin Heavy Chainmentioning
confidence: 99%
“…Furthermore, Herrera-Rodríguez et al [ 61 ▪ ] conducted a systematic review and found that multiple site mutations in MYH7 gene were associated with SCD of HCM, including p. Arg 453 Cys, p. Arg 1045 Leu, p. Arg 719 Trp, p. Asn 391 Thr, p. Gly 716 Arg, p. Arg 403 Gln, p. Arg 453 Cys, p. Glu 848 Gly and p. Asn 391 Thr. Moreover, study from Liu et al [ 62 ] found that thr 446 pro and phe 468 leu mutations of MYH7 gene can also lead to SCD.…”
Section: Gene Mutationsmentioning
confidence: 99%
“…Although there has been much research on the molecular genetics of HCM in recent years, research on the correlation between MYH7 gene variants and HCM is still insufficient in China [ 10 , 11 ]. In this study, we found a pedigree with an "uncertain significance" variant of MYH7 .…”
Section: Introductionmentioning
confidence: 99%